Peer bonds and nature’s embrace: exploring the influence of pet caregiving on social well-being and nature connection among Taiwanese children - Tseng, Tzuhui Angie; Fang, Hsiao-Yen; Shen, Ching-Cheng; Chang, Yun-Chen (Frontiers in Public Health, 2024)
This study investigated the associations between pet-ownership on nature engagement, interpersonal relationships, and well-being among 471 Taiwanese children aged 11–12, across different genders. The findings revealed that interactions with pets, primarily in the form of caregiving, enhanced empathy toward nature, notably among female participants from various racial and ethnic backgrounds, although direct contact with nature was generally limited. In terms of interpersonal relationships, family bonds were significant, with boys reporting stronger connections. Children who had previously or were currently owning pets displayed increased empathy toward the natural environment. The study highlighted a significant predictive relationship between children’s connection to nature and their development of interpersonal relationships, with peer relationships being particularly influential in predicting children’s well-being. These results underscored the importance of pet caregiving and peer interactions in the emotional and social development of children.